2020
DOI: 10.2174/1874350102013010115
|View full text |Cite
|
Sign up to set email alerts
|

Meaningfulness of Work and Employee Engagement: The Role of Affective Commitment

Abstract: Background: Meaningfulness of work leads to positive job-related consequences, such as engaged, satisfied, productive, trustworthy, and devoted employees. Purpose: The main purpose of this research was to study the relationship between meaningfulness of work, employee engagement, and affective commitment. Further, this study is also examined the mediating influence of affective commitment on the relationship between meaningfulness of work and employee engagement. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 46 publications
4
20
0
4
Order By: Relevance
“…Normative commitment and continuous commitment involve the perceived responsibility and the perceived demission cost, respectively. Among the three types of commitment, affective commitment is hypothesized to have the largest effect on personal work attitude [ 12 , 14 ]. This is because the characteristics of affective commitment include attachment to the organization, identification with the organization’s culture, and the willingness to continue to be a member of the organization [ 26 ].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 4 more Smart Citations
“…Normative commitment and continuous commitment involve the perceived responsibility and the perceived demission cost, respectively. Among the three types of commitment, affective commitment is hypothesized to have the largest effect on personal work attitude [ 12 , 14 ]. This is because the characteristics of affective commitment include attachment to the organization, identification with the organization’s culture, and the willingness to continue to be a member of the organization [ 26 ].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…This is because the characteristics of affective commitment include attachment to the organization, identification with the organization’s culture, and the willingness to continue to be a member of the organization [ 26 ]. Compared with normative commitment and continuous commitment, individuals with affective commitment have more motivation to realize work successes and contribute more to their organizations [ 12 , 25 ]. Past research has indicated that affective commitment positively affects personal outcomes, such as work output [ 13 , 14 ].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 3 more Smart Citations